Formulation Of Eye Shadow Cream With Ethanol Extract Of Red Spinach (Amaranthus tricolor L.) Leaves As A Dye - Suryani, Monica; Ivan Elisabeth Purba; Cut Masyithah Thaib; Putri Sion Simbolon (Sean Institute, 2022)
Anthocyanin is one of the chemical compounds contained in read spinach leaf (Amaranthus tricolor L.) and plays an important role in providing color. The red spinach leaf ethanol extract is very well used as a natural dye in eye shadow cream preparations. The purpose of this study was to formulate eye shadow cream preparations using ethanol extract of red spinach leaves as a dye, find out whether the preparation of eye shadow cream with ethanol extract of red spinach leaves meets the quality requirements and evaluate the irritation test on the skin. The eye shadow cream was formulated using talc, titanium dioxide, beeswax, Na2EDTA, glycerin, methyl paraben, propyl paraben, parfum, and paraffin liq with varying concentrations of ethanol extract of red spinach leaf ethanol extract 0%, 6%, 10%, and 14%. Physical quality examination includes organoleptic test, homogeneity test, smear test, cream type test, spreadability tes, pH test, viscosity test, stability test and irritation test and preference test for eye shadow cream preparations. The results of research conducted at a concentration of 0% gave a white color, a concentration of 6% gave a pink color, a concentration of 10% gave a light pink color, and a concentration of 14% gave a deep pink color. The conclusion of this study is ethanol extract of red spinach leaves can be used as a colorant in eye shadow cream preparations, meets the quality requirements of the preparation and does not cause irritation when used.